دور أقسام المکتبات بالجامعات المصریة فى خدمة المجتمع : دراسة میدانیة لواقعها ووضع تصور للنهوض بها - د. نصار رمضان عمر (المجلة الدولية لعلوم المكتبات والمعلومات)
The role of libraries departments, as all university institutions, focuses mainlyupon education, scientific research and community service. The purpose of thisstudy is to highlight the role of libraries departments in the Egyptian universities incommunity service. It examines the status of community service in librariesdepartments, as well as the obstacles that impede the implementation ofcommunity service programs in the appropriate manner.The study was applied on fourteen departments of the Egyptian librariesdepartments. It was found that the interest in serving community within thelibraries departments in Egyptian Universities is medium. There are nostatistically significant differences in the interest of libraries attributed to thedepartments’ years of experience, the staff’s scientific level, or the majority’sgender.Therefore, the researcher has developed a guiding vision to help librariesdepartments to serve the community appropriately